Generalised predictive current‐mode control of passive front‐end boost‐type converters. Issue 3 (10th January 2021) - Judewicz, M. G.; González, S. A.; Fischer, J. R.; Martínez, J. F.; Carrica, D. O.
Abstract: In this work, an average current‐mode control strategy based on a generalised predictive control formulation for passive front‐end three‐phase boost‐type converters is proposed. A novel design procedure for the generalised predictive control strategy is introduced which considers both the cost function and disturbance model as design parameters to set the controller's dynamic response and robustness against component variations. A maximum robustness criterion was used for achieving stability up to a 70% inductance reduction with maximum possible bandwidth. The proposed strategy was compared against both a PI and a predictive deadbeat average current‐mode control using both simulations and experimental results on a 2 -kW converter. The generalised predictive control presented less performance variations between different operating points than the PI controller. Also, the proposed strategy is more robust than the predictive deadbeat strategy, showing a better transient response with a 50% inductance reduction and remained stable for a 71% inductance reduction, while the predictive deadbeat could not. Finally, the proposed strategy achieved a 1.4% output voltage load transient response for a 595 W load power step, and a 2.8% output voltage line transient response for a 100 V input voltage step, outperforming existing state‐of‐the‐art strategies.